PERCENTAGE OF PHYSICAL CARCASES IN QUAIL THAT STARFRUIT LEAF EXTRACT (Averrhoa Bilimbi L) - D., Wicaksono; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2023)
The purpose of this study was to determine the physical percentage of quail given the leaf      The purpose of this study was to determine the physical percentage of quail given the leaf extract of star fruit ( Averrhoa Bilimbi L ).  This research was conducted at the Teaching Farm Sesetan and the Poultry Livestock Laboratory, Faculty of Animal Science, Udayana University.  The design used was a completely randomized design (CRD) with 4 treatments and 4 replications. Each replication used 4 quail at 4 weeks of age. The treatment given was drinking water without starfruit leaf extract (A) as a control. Giving drinking water with starfruit leaf extract as much as 2%, 4%, and 6% as treatments B, C, and D. The results showed that the of starfruit leaf extract in drinking water was not significantly different (P>0,05) in slaughter weight, carcass weight, carcass percentage, and carcass physical percentage. From the results of this study it can be concluded that the administration of starfruit leaf extract ( Averrhoa Bilimbi L ) by giving as much as 2%, 4% and 6% in drinking water did not effect on slaughter weight, carcass weight, carcass percentage, and carcass physical percentage (meat, bones, skin) quail 5 weeks old.   Keywords: drinking water, quail, starfruit leaf extract